APPLICATION OF THE POINT MERGE SYSTEM TO IMPROVE AIR TRAFFIC CONTROL EFFICIENCY UNDER INCREASING FLIGHT INTENSITY (Web of Technology: Multidimensional Research Journal, 2025)
With the steady growth in global air traffic, air navigation systems face increasing pressure to ensure safe, efficient, and timely aircraft sequencing and separation. This article explores the application of the Point Merge System (PMS) as a modern air traffic control technique designed to enhance operational efficiency under conditions of high flight intensity. PMS provides a structured and predictable approach to aircraft sequencing through predefined navigation points and systematic merge techniques, thereby reducing controller workload and minimizing delays. The paper analyzes the benefits of PMS in terms of fuel efficiency, airspace capacity, and environmental sustainability. Furthermore, it discusses the integration of PMS with performance-based navigation (PBN) and automation technologies as a scalable solution for future air traffic management.